2018
DOI: 10.1111/1467-8551.12313
|View full text |Cite
|
Sign up to set email alerts
|

When Many Davids Collaborate with One Goliath: How Inter‐organizational Networks (Fail to) Manage Size Differentials

Abstract: How do organizations of vastly different size collaborate in order to achieve a common goal? While this poses less of a problem when the network is orchestrated by a classic lead firm, in networks exhibiting a shared governance mode, where leadership responsibilities are more or less equally distributed, size differentials present a critical management challenge. In this paper, we contribute to the literature on coordination in and of interorganizational arrangements by emphasizing the so far largely neglected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Second, prior research has shown that effective coordination depends on the fit between coordination needs and coordination mechanisms (Gulati et al, 2012; Oliveira & Lumineau, 2017), but offers limited insights into how a network orchestrator relies on formal and informal coordination to govern inter‐organizational networks (Fortwengel & Sydow, 2020; Provan et al, 2007; Reypens et al, 2021). This is important given that our data showed that fit between task complexity and network governance contributes to high network performance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, prior research has shown that effective coordination depends on the fit between coordination needs and coordination mechanisms (Gulati et al, 2012; Oliveira & Lumineau, 2017), but offers limited insights into how a network orchestrator relies on formal and informal coordination to govern inter‐organizational networks (Fortwengel & Sydow, 2020; Provan et al, 2007; Reypens et al, 2021). This is important given that our data showed that fit between task complexity and network governance contributes to high network performance.…”
Section: Discussionmentioning
confidence: 99%
“…Second, a key, but poorly understood, governance activity performed by the network orchestrator, is how coordination is intentionally established (Pathak et al, 2014). Extant studies provided very limited insights about the formal and informal coordination undertaken by the network orchestrator on ensuring network performance (Fortwengel & Sydow, 2020; Reypens et al, 2021). Our study unpacks the mode of coordination (formal or informal), the intensity of coordination (active or passive), and fit with the form of governance form (shared or lead).…”
Section: Conceptual Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Documents. Interviews are a valuable way of generating deep insights into the underlying processes and practices of an empirical phenomenon such as inter-organisational collaboration and have been used to investigate network dynamics and inter-organisational collaborations in previous studies (e.g., Majchrzak et al, 2015;Fortwengel and Sydow, 2018). However, as pointed out by Eisenhardt and Graebner (2007), they are subject to a number of weaknesses including subjectivity and retrospective sense-making.…”
Section: Data Collectionmentioning
confidence: 99%